Fifty Definitions of English Learner: A Proposed Solution to Inconsistent State-by-State Systems in the United States for Classifying Students Who Speak English as a Second Language - Rolf Straubhaar; Pedro R. Portes (Educational Considerations, 2022)
Although nearly one in 10 U.S. students is an English Learner (or EL), the definition of the term EL varies considerably from state to state, as does the means of assessing English language proficiency and the period of time for which the label is applied to individual students. As EL populations are growing throughout the U.S., both in school systems familiar with teaching ELs and in systems that do not have such experience, it is urgent that the methods by which this population is identified and by which its needs are met in acquiring English language proficiency are backed up by evidence and, ideally, standardized at the national level. In this article, after reviewing the current decentralized climate of EL identification, classification and reclassification, we propose a new definition of English Learner that both resolves inconsistencies in current state-level practices and would include many practicing ELs who are often excluded from current state-level definitions.
Keywords: English learners; ESL; EL; language policy; student assessment